A kind of grace : a treasury of sportswriting by women (Berkeley, CA : Zenobia Press, 1994)
An anthology of articles about women in sports written by leading female sportswriters from the U.S., Canada, and the United Kingdom.
Publisher's Weekly.
School Library Journal.
Young Adult
Keywords: Sports journalism; Sportswriters; Women athletes; Sports journalism; Sportswriters; Women athletes